The Impact of Perceived Social Support and Emotion Regulation on the Psychological Well-Being of Islamic Boarding School Teachers - Abdul Khodir; Damajanti Kusuma Dewi; Riza Noviana Khoirunnisa (Bulletin of Counseling and Psychotherapy, 2026)
This study aims to examine the effect of perceived social support and emotion regulation on the psychological well-being of teachers in an Islamic boarding school (pesantren) context. The study employed a quantitative cross-sectional design involving 264 permanent teachers from an integrated Islamic boarding school foundation in East Java, Indonesia. Data were collected using three standardized instruments: Ryff’s Scales of Psychological Well-Being (42 items), the Multidimensional Scale of Perceived Social Support/MSPSS (12 items), and the Emotion Regulation Questionnaire/ERQ (10 items). Data were analyzed using multiple linear regression after all classical assumptions were met. The results revealed that perceived social support and emotion regulation simultaneously had a positive and significant effect on teachers’ psychological well-being, with an F value of 160.358 and p < 0.001. The coefficient of determination indicated that these two variables explained 64.9% of the variance in psychological well-being (R = 0.806; R² = 0.649). These findings demonstrate that the psychological well-being of pesantren teachers is shaped not only by internal personal resources but also by supportive social environments. Therefore, strengthening social support and providing emotion regulation training are important strategies for promoting teachers’ mental health and sustaining educational quality in pesantren settings.